Pengembangan Panduan Microteaching Berbasis Outcome Based Education (OBE) - Neolaka, Frengky; Halek, Erlin Fatima; Ramadhan, Fitra; Naimnule, Lusia (Biocaster : Jurnal Kajian Biologi, 2025)
The development of the Outcome Based Education (OBE) curriculum encourages universities to adapt by implementing OBE-based learning. This research aims to develop an OBE-based microteaching handbook that has been validated by material experts and media experts, and tested to users. The research method used is Research and Development (R&D) with a 3D development model, namely Define, Design, and Develop. The trial was carried out on lecturers and students involved in microteaching courses. The results of validation by material experts obtained an average score of 86.75% with the very feasible category, while the validation results by media experts obtained a score of 86.83% with the very feasible category. The results of the trial obtained a score of 94% with a very feasible category. Thus, it can be concluded that the OBE-based microteaching handbook developed is very suitable for use and is expected to be a practical guide in improving teaching skills based on graduate learning outcomes.